The Mammary Gland Carcinogens: The Role of Metal Compounds and Organic Solvents - Stephen Juma Mulware (International Journal of Breast Cancer)
The increased rate of breast cancer incidences especially among postmenopausal women has been reported in recent decades. Despite the fact that women who inherited mutations in the BRCA1 and BRCA2 genes have a high risk of developing breast cancer, studies have also shown that significant exposure to certain metal compounds and organic solvents also increases the risks of mammary gland carcinogenesis. While physiological properties govern the uptake, intracellular distribution, and binding of metal compounds, their interaction with proteins seems to be the most relevant process for metal carcinogenicity than biding to DNA. The four most predominant mechanisms for metal carcinogenicity include (1) interference with cellular redox regulation and induction of oxidative stress, (2) inhibition of major DNA repair, (3) deregulation of cell proliferation, and (4) epigenetic inactivation of genes by DNA hypermethylation. On the other hand, most organic solvents are highly lipophilic and are biotransformed mainly in the liver and the kidney through a series of oxidative and reductive reactions, some of which result in bioactivation. The breast physiology, notably the parenchyma, is embedded in a fat depot capable of storing lipophilic xenobiotics. This paper reviews the role of metal compounds and organic solvents in breast cancer development.